Women with nonischemic cardiomyopathy have a favorable prognosis and a better left ventricular remodeling than men after cardiac resynchronization therapy. Issue 4 (April 2016) - Cipriani, Manlio; Landolina, Maurizio; Oliva, Fabrizio; Ghio, Stefano; Vargiu, Sara; Rordorf, Roberto; Raineri, Claudia; Ammirati, Enrico; Petracci, Barbara; Campo, Claudia; Bisetti, Silvia; Lunati, Maurizio
Abstract : Aims: Cardiac resynchronization therapy (CRT) is a well established therapy in heart failure patients who are on optimal medical therapy and have reduced left ventricular ejection fraction (LVEF) and wide QRS complexes. Although women and patients with nonischemic cardiomyopathy are under-represented in CRT trials and registries, there is evidence that these two groups of patients can benefit more from CRT. The aim of our analysis was to investigate the impact of female sex on mortality in a population that included a high percentage of patients (61%) with nonischemic cardiomyopathy. Methods: We analyzed data on 507 consecutive patients (20% women) who received CRT at two Italian Heart Transplant centers and were followed up for a maximum of 48 months. Results: After multivariate adjustment, women showed a trend toward better survival with regard to all-cause mortality [hazard ratio (HR) 0.32, confidence interval (CI) 0.10–1.04; P  = 0.059]. However, this benefit was limited to nonischemic patients with regard to all-cause mortality (HR 0.20, CI 0.05–0.87, P  = 0.032) and cardiovascular mortality (HR 0.14, CI 0.02–1.05, P  = 0.056). Conclusion: Female CRT recipients, at mid-term, have a favorable prognosis than male patients and this benefit appears to be more evident in nonischemic patients. Thus, we strongly believe that the apparent under-utilization of CRT in females is an anomaly that should be corrected.